Beyond the End - Olanipekun, Olayemi (Evans Brothers (Nigeria Publishers) Limited, 2012)
A Week to her wedding ceremony, Patience accidentally discovers she has contracted HIV virus. After disclosing her status to Tony, her fiance, he also goes for the same test but finds out he was HIV negative! Will they still go ahead with the wedding? Or will this be the end of their long and devoted love relationship?
Keywords: Courtship; Drama; Nigeria